A PLK1 inhibitor, RO3280, suppresses proliferation of SNU-16 gastric cancer cells via apoptosis (Bangladesh Journal of Pharmacology, 2024)
This study examines the anti-tumor, pro-apoptotic, and genotoxic effects of polo-like kinase 1 (PLK1) inhibitor RO3280 on the gastric cancer cell line SNU-16. Using the XTT assay, the antiproliferative effect of the compound was identified and showed a significant antiproliferative effect (p